Narrativer i Islamisk Stats propagandamagasin, Rumiyah – en digital tilgang til diskursanalyse - Kiis, Emma Elisabeth (Nordisk Tidsskrift for Kriminalvidenskab, 2020)
Abstract This article uses messages communicated through the Islamic State’s propaganda magazine, Rumiyah, to explore the applicability of text mining methods in discourse analysis. The repertoire of narratives used in Rumiyah is examined through the theoretical framework of Narrative Criminology in combination with Discourse Theory, as presented by Ernesto Laclau and Chantal Mouffe. Techniques and methods from the field of digital text mining are also applied. The current article therefore has two sections: a quantitatively-deduced discourse analysis and a qualitatively-deduced discourse analysis.